2022
DOI: 10.1038/s41598-022-17720-z
|View full text |Cite
|
Sign up to set email alerts
|

Identifying subtypes of HIV/AIDS-related symptoms in China using latent profile analysis and symptom networks

Abstract: The identification of subgroups of people living with HIV in China based on the severity of symptom clusters and individual symptoms is crucial to determine group-specific symptom management strategies. Participants reported 27 highly prevalent HIV/AIDS-related symptoms. Latent profile analysis based on symptom severity was used to identify person-centered subtypes of HIV/AIDS-related symptoms. Symptom networks were compared among subgroups identified by latent profile analysis. A total of 2927 eligible people… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…However, the event, by virtue of its scale and duration, also initiated a socially shared chronic stress. It was therefore interesting that within the same clinical sample in the similar context of uncontrollable external circumstances, we observed two such contrasting profiles, i.e., flourishing versus languishing [ 47 ] , which is another argument for PLWH being a heterogeneous patient group with regard to adaptation not only to HIV infection but also in terms of general functioning [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the event, by virtue of its scale and duration, also initiated a socially shared chronic stress. It was therefore interesting that within the same clinical sample in the similar context of uncontrollable external circumstances, we observed two such contrasting profiles, i.e., flourishing versus languishing [ 47 ] , which is another argument for PLWH being a heterogeneous patient group with regard to adaptation not only to HIV infection but also in terms of general functioning [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have found that this latter tendency is a derivative of still existing, strong stigmatization of PLWH (see these meta-analyses: [ 16 , 17 ]). At the same time, several authors have observed that PLWH are also a heterogeneous patient group with respect to coping and adapting to their illness [ 18 20 ]. Specifically, although they share the same medical diagnosis (i.e., HIV infection), PLWH display different trajectories in their psychological functioning over time (e.g., [ 21 , 22 ]).…”
Section: Introductionmentioning
confidence: 99%